Aquaculture Perspective of Multi-Use Sites in the Open Ocean 2017
DOI: 10.1007/978-3-319-51159-7_8
|View full text |Cite
|
Sign up to set email alerts
|

The Socio-economic Dimensions of Offshore Aquaculture in a Multi-use Setting

Abstract: Decision-making within the marine realm is a complex process, which endorses ecological, societal and economic needs and they must therefore be managed jointly. Much of the formerly "free oceans" is nowadays subject to intensive uses, thus making the need to optimise the management of the resources within a multifunctional and multi-use(r) context apparent. The high competition for functions and uses of inshore and nearshore waters has given strong incentives to investigate the opportunities of moving industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Knapp (2008) projects that an offshore sh farm with a yearly production of 10 million pounds (about 4,500 tonnes) in U.S. waters would yield an IRR of 22% (pp. [42][43]. Thomas et al (2019) propose an offshore sh farm model for the Caribbean that they found to be both technically and economically feasible and which could produce almost half the amount of seafood that is produced by wild capture sheries globally.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Knapp (2008) projects that an offshore sh farm with a yearly production of 10 million pounds (about 4,500 tonnes) in U.S. waters would yield an IRR of 22% (pp. [42][43]. Thomas et al (2019) propose an offshore sh farm model for the Caribbean that they found to be both technically and economically feasible and which could produce almost half the amount of seafood that is produced by wild capture sheries globally.…”
Section: Literature Reviewmentioning
confidence: 99%
“…53 Social typologies tend to be more general, focussed on key principles, factors or human dimensions to consider. [54][55][56] Other typologies have used ecosystem services to differentiate values provided. [57][58][59] In section 2.0, we detail the background and logic of our conceptual framework premised on commons governance theories.…”
Section: F I G U R Ementioning
confidence: 99%
“…fed, un‐fed, auto‐trophic) 53 . Social typologies tend to be more general, focussed on key principles, factors or human dimensions to consider 54‐56 . Other typologies have used ecosystem services to differentiate values provided 57‐59 …”
Section: Introductionmentioning
confidence: 99%
“…The impacts of aquaculture on the economy of rural communities are key issues for sustainable development policies (Béné et al, 2016, Au-IBAR, 2017) [45,46] , since, the establishment of aquaculture businesses in a region can influence the availability of input factors like skilled labor, specialized suppliers, education programs, and other infrastructure (Krause and Mikkelsen, 2017) [47] . Over time, however, the development and growth of the aquaculture sector may stimulate the growth of other more or less related industries in the region, including the development of service and value chain activities (Aslesen and Isaksen 2007) [48] .…”
Section: The Economic Dimensionmentioning
confidence: 99%